PENGARUH CORPORATE GOVERNANCE DAN KEBIJAKAN DIVIDEN TERHADAP STRUKTUR MODAL (STUDI EMPIRIS PERUSAHAAN ENERGI DI BURSA EFEK INDONESIA PERIODE 2018-2022) - Mahira; Endah Finatariani (Jurnal Nusa Akuntansi, 2026)
This research aims to provide empirical evidence of the influence of corporate governance and dividend policy on capital structure. This research uses a quantitative approach and the data used is secondary data. The population in this study are Energy Companies listed on the Indonesia Stock Exchange for the 20182022 period. The method for determining the sample used purposive sampling. A total of 9 companies were obtained over a 5 year period so that the total obtained was 45 sample data. The method used is multiple linear regression statistical tests descriptive, panel data regression model analysis, selected model selection test are the Fixed Effect Model, classical assumption test, multiple linear test and test hypothesis with the help of Eviews version 12 data processing. Based on test results The hypothesis simultaneously shows that Corporate Governance and Dividend Policy jointly influence Capital Structure. The results of partial hypothesis testing show that Corporate Governance, which is proxied by Institutional Ownership, has an effect on Capital Structure, while dividend policy has no effect on Capital Structure.